The awareness and knowledge of alternative Islamic treatment: a case study in Malaysia / Norazlinda Mohammad ... [et al.] - Mohammad, Norazlinda; Abdul Karim Zamri, Norena; Abdullah, Siti Nur Fadzilah; Radzi, Raha (Faculty of Art and Design, 2020)
Technological advances and evolution in medicine have evolved and led humans to find alternative methods of modern medicine. Alternative treatment centers based on either "Islamic Treatment" or traditional ones are becoming more and more popular over time. Alternative treatments of Islam are treatments based on ruqyah, aura, inner, and homeopathy. In line with this rapid alternative to Islamic medicine, the Malaysian government supports Traditional and Complementary Medicine (TCM) in connection with any traditional medical practice among the local community except for medical or dental practices registered and recognized under the Malaysian healthcare system. However, to this day, the awareness, exposure and knowledge of alternative Islamic medicine are still in small scale and very limited in society. This issue needs to be taken into account for the importance of exposure and knowledge to the community not only to the Muslim community, but to all Malaysians. As such, this research aims to raise awareness and make research findings a platform to provide comprehensive information to the public. This can change the perception and resolve the community's doubts on alternative Islamic medicine as well as enhance the development of alternative Islamic medicine by offering a 'one-stop-center' hub for the needs of patients in need of alternative treatment. This study will use qualitative approach by interviewing the founder and practitioner of Islamic medicine Darul Ansar center and also observation method by observing the practice of medicine or treatment in accordance to Islamic syariah. The interview will be using thematic analysis whereby the data will be gathered and analysed.